Influence of Gender, Dispositional Optimism, and Coping Strategies on Appearance-Related Distress Among Swedish Adults With Cleft Lip and Palate. (June 2022) - Paganini, Anna; Persson, Martin; Mark, Hans
Objective: To investigate the influence of gender, dispositional optimism, and coping strategies on appearance-related distress among individuals with unilateral cleft lip and palate (UCLP). Design: Cross-sectional design with self-report questionnaires analyzed primarily with Spearman correlations ( r s ) and multivariate regression analyses. Setting: A tertiary cleft center in Sweden. Participants: Eighty individuals with UCLP born 1966 to 1986. The mean age for men (n = 50) and women (n = 30) was 38.8 and 37.4 years, respectively. Main Outcome Measures: The Derriford Appearance Scale 24 measured appearance-related distress, the Life Orientation Test–Revised, short version measured dispositional optimism and pessimism, and the Coping Orientation to Problems Experienced, short version included 14 coping strategies. Results: Women had higher appearance-related distress than men, which was significantly ( P < .05) related to self-blame ( r s = 0.59), pessimism ( r s = 0.59), and low optimism ( r s = −0.56). Men's appearance-related distress was significantly associated with low active coping ( r s = 0.35), low use of emotional support ( r s = 0.29), denial ( r s = 0.39), behavioral disengagement ( r s = 0.41), and pessimism ( r s = 0.28). The only significant gender interaction reflected greater impact of optimism in reducing appearance-related distress for women (β = −0.06). Conclusions: This study showed that high levels of dispositional optimism decrease appearance-related distress, particularly for women. The coping strategies used differed between men and women, and the results suggest that both gender and psychosocial facto r s need to be considered in regard to appearance-related distress among individuals with UCLP in both clinical and research settings. A possible way to decrease distress is to strengthen positive coping strategies and dispositional optimism.